2000
DOI: 10.1182/blood.v95.12.3653
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary cutaneous CD30+lymphoproliferative disorders: a report from the Dutch Cutaneous Lymphoma Group on the long-term follow-up data of 219 patients and guidelines for diagnosis and treatment

Abstract: To evaluate our diagnostic and therapeutic guidelines, clinical and long-term follow-up data of 219 patients with primary or secondary cutaneous CD30+ lymphoproliferative disorders were evaluated. The study group included 118 patients with lymphomatoid papulosis (LyP; group 1), 79 patients with primary cutaneous CD30+ large T-cell lymphoma (LTCL; group 2), 11 patients with CD30+ LTCL and skin and regional lymph node involvement (group 3), and 11 patients with secondary cutaneous CD30+ LTCL (group 4). Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
558
10
42

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 701 publications
(632 citation statements)
references
References 25 publications
22
558
10
42
Order By: Relevance
“…Previous studies reported that approximately 15-20% of the patients with C-ALCL have multifocal lesions. [2][3][4] However, from the 283 patients with C-ALCL that had been included in the Dutch Cutaneous Lymphoma Registry between 1985 and 2017, only 28 had multifocal skin lesions at first presentation (10%), and only nine of them had first presented with more than five affected skin sites (3%). Consistent with previous studies, patients with multifocal C-ALCL had a much higher relapse rate (67%), more often developed extracutaneous disease (33%) and had a lower 5-year DSS (78%) and 5-year OS (66%) compared with patients with solitary or localized C-ALCL (40% relapse rate: 10% extracutaneous relapse rate; 5year DSS 95% and 5-year OS 85%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies reported that approximately 15-20% of the patients with C-ALCL have multifocal lesions. [2][3][4] However, from the 283 patients with C-ALCL that had been included in the Dutch Cutaneous Lymphoma Registry between 1985 and 2017, only 28 had multifocal skin lesions at first presentation (10%), and only nine of them had first presented with more than five affected skin sites (3%). Consistent with previous studies, patients with multifocal C-ALCL had a much higher relapse rate (67%), more often developed extracutaneous disease (33%) and had a lower 5-year DSS (78%) and 5-year OS (66%) compared with patients with solitary or localized C-ALCL (40% relapse rate: 10% extracutaneous relapse rate; 5year DSS 95% and 5-year OS 85%).…”
Section: Discussionmentioning
confidence: 99%
“…2 Approximately 15-20% of the patients with C-ALCL present with multifocal lesions involving multiple anatomical areas. [2][3][4] Although there is broad consensus that radiotherapy is the first choice of treatment in solitary or localized C-ALCL, there is uncertainty about the optimal treatment of patients with multifocal C-ALCL. 1,2,[5][6][7][8] Initial studies suggested that these patients should be treated with doxorubicin-based chemotherapy.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Clinically, most C-ALCL patients present with limited disease characterized by solitary or localized skin nodules or tumours, while multicentric cutaneous disease is also seen in approximately 20% of cases, and lesions may show partial or complete spontaneous regression in over 25% of patients with frequent relapses. 3,5 There are clinicopathological similarities between C-ALCL and LyP; 6 however, LyP runs a benign clini-cal course with spontaneous disappearance of individual skin lesions in all cases and hence belongs to a self-resolving form of CTCL. 7 LyP typically occurs in early adulthood and presents with recurrent nodules and papules at distant sites, usually less than 1 cm in diameter, which become necrotic before resolving to form an atrophic scar.…”
Section: Discussionmentioning
confidence: 99%